Sistema de alerta para estudiantes con discapacidad visual en la UTM - Cruz Felipe, Marely del Rosario; Pinargote Ortega, Jenmer Maricela; Demera Ureta, Gabriel Primitivo; Vera Zambrano, Edisson Manuel; Mosquera Alcívar, Rosa Antonia (Revista Científica, 2018)
In the transfer of students with visual disabilities at the Technical University of Manabí (UTM) accidents have been reported when going through some ramps and other obstacles, especially on rainy days. This article belongs to an investigation into the realization of an alert system for students with visual disabilities. The objective of the implementation of this system is to guide students with visual disabilities on different obstacles that exist in their transfer through the university. To carry out the implementation of this system, the alert systems and the technologies that are currently used as a result of a recording studio in the national and international scope were analyzed, the tools and technologies used in the developed solution are described. (Definition, technologies for the change of people, software, programming languages, etc.) that allowed an efficient implementation in a short time of the proposed system by means of RFID (Radio Frequency Identification) technology. The above is reflected in the positive orientation for the transfer of 32 students with visual disabilities through the university and by those who have contributed to improving their quality of life.